Discovery and characterization of JMJD6 as a novel oncogene. - Lee, Yi Fang. (2012)
The pathogenesis of breast cancer involves a multitude of genetic alterations affecting the regulation of cell growth, survival, invasion and metastasis. To discover such novel oncogenes, we analyzed comprehensive gene expression profiles of breast tumors from several breast cancer patient cohorts for correlations between gene expression and distant metastasis-free survival. Several oncogene candidates were identified for siRNA-mediated functional screening. Jumonji Domain Containing 6 Protein (JMJD6), a putative histone arginine demethylase and RNA binding factor, was one of the genes robustly associated with poor survival in multiple cohorts. Immunohistochemical analysis of JMJD6 in tissue microarrays suggested that its high expression significantly correlated with grade and estrogen receptor negativity. Over-expression of JMJD6 in MCF-7 led to increased proliferation and motility, while in contrast, siRNA-mediated knock-down suppressed cell division and decreased motility. Microarray analysis of gene expression changes induced by JMJD6 suggested that JMJD6 led to increased expression of cell cycle genes and downregulation of anti-proliferative factor, TGF-beta (TGF-β). We confirmed that siRNA-mediated knock-down of JMJD6 increased TGF-β 2 secretion whereas JMJD6 over-expression reduced it. Since TGF-βs have been implicated in cell cycle arrest in many epithelial cells, we propose that JMJD6 may influence cell growth primarily via this pathway. Further clinical correlation of JMJD6 and TGF-β2 in expression corroborated our cell-based observations. Although JMJD6 was reportedly a histone demethylase, our study of JMJD6 based on this function suggested that JMJD6 may not be a histone demethylase. On the other hand, our preliminary study of JMJD6 as a RNA-binding factor had yielded some novel possibilities of JMJD6 in RNA regulation. Collectively, these results suggest that the extrapolation of gene-survival associations in primary tumors to phenotypic analysis in vitro holds promise as a platform for understanding of new mechanisms in tumorigenesis, as well as discover new therapeutic targets.